Metal-organic framework nanoagent induces cuproptosis for effective immunotherapy of malignant glioblastoma - Huang, Qian-Xiao; Liang, Jun-Long; Chen, Qi-Wen; Jin, Xiao-Kang; Niu, Mei-Ting; Dong, Cheng-Yuan; Zhang, Xian-Zheng (Nano today, 2023)
Glioblastoma (GBM) is an aggressive brain cancer with an immunosuppressive tumor microenvironment. Here, a copper-based nanoplatform BSO-CAT@MOF-199 @DDM (BCMD) is constructed for mediating cuproptosis and subsequently promoting immunotherapy of glioblastoma. Specifically, BCMD can be degraded in the slightly acidic tumor environment to release Cu2+, which will be further reduced to toxic Cu+ to induce cuproptosis under the regulation of high level of ferredoxin 1 (FDX1). Meanwhile, buthionine-sulfoximine (BSO) and catalase (CAT) released from BCMD can reduce the glutathione (GSH) synthesis and increase O2 content in tumor cells, thereby rendering the tumor cells more sensitive to BCMD-mediated cuproptosis. In vivo experiments show that BCMD mediated cuproptosis can trigger the immunogenic cell death (ICD) to increase the infiltration of cytotoxic T lymphocytes and reverse the immunosuppressive microenvironment of glioblastoma to enhance tumoricidal immunity. Furthermore, anti-tumor therapeutic efficiency of immune checkpoint blockade (ICB) therapy is significantly enhanced by combining BCMD with αPD-L1. [Display omitted] •Served as a non-invasive nasal administration preparation to bypass blood brain barrier and reduce systemic side effects.•Induced cuproptosis under the regulation of high level of ferredoxin 1 (FDX1) in glioblastoma.•Reversed the immunosuppressive tumor microenvironment to enhance effective anti-tumor effect.•Good biological safety and clinical application prospect.